Tanggapan Pertumbuhan dan Hasil Varietas Jagung Hibrida terhadap Pemupukan Nitrogen dalam Sistem Agroforestri - Surya Adam Yoga Aditya; Dody Kastono; Taufan Alam (Vegetalika, 2025)
The main issue with hybrid maize is its low nitrogen uptake, ranging from 30% to 50%. This study aims to improve nitrogen fertilization efficiency by selecting hybrid maize varieties in an agroforestry system. The research was conducted from January to April 2024 at the Menggoran Forest Management Resort (RPH Menggoran), Playen, Gunungkidul, Yogyakarta. A split-plot experimental design was employed, with 15 hybrid maize varieties as the main plot and urea fertilization as the subplot. The results revealed that nitrogen fertilization in the agroforestry system increased grain weight by 25%–68% compared to no fertilization. The highest grain weight was observed in the Pertiwi 6 and KS-89 Monster varieties, even without nitrogen fertilization. Meanwhile, the ADV Jago, Bomber R101, Turbo B-59, Si Tampan, and Twinn 1 varieties produced high grain weights when nitrogen fertilizer was applied.